Trinidad Cocoa - Cocoa tree in fruit - (:unkn) unknown (My University, 2010)
A picture of a cocoa tree full of its fruit ready for harvest. Also printed on the postcard is the note "By courtesy of Messrs. Cadbury Bros. Ltd."
Colour: Black and White; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa; Agriculture; Theobroma cocoa